2017
DOI: 10.1186/s12875-017-0657-6
|View full text |Cite
|
Sign up to set email alerts
|

An after hours gp clinic in regional Australia: appropriateness of presentations and impact on local emergency department presentations

Abstract: BackgroundAfter hours general practice clinics provide medical attention for clients with non-emergency situations but are seeking immediate treatment and unable to wait for a general practitioner during routine opening hours. Evidence on the impact that after hours clinics have on emergency department presentations is equivocal. This study explored outcomes of the Bathurst After Hours General Practice Clinic (BAHGPC). Specifically it examined: clients’ perceived urgency of, and satisfaction with their present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…In Australia, general practitioners (GPs) are usually the first point of healthcare contact and vital to managing disease and providing continuity of care. Increasingly, patients expect availability of 24-h care, presenting after usual practice hours to after-hours primary care services or to hospital emergency departments (ED) (Ifediora and Rogers 2017;Payne et al 2017). The number of ED presentations increased by 67% from 4.5 million in financial year 2004-05 to 7.5 million in 2015-16 (Australian Institute of Health and Welfare 2009; Australian Institute of Health and Welfare 2016), with the rate of increase exceeding the rate of population growth (Payne et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Australia, general practitioners (GPs) are usually the first point of healthcare contact and vital to managing disease and providing continuity of care. Increasingly, patients expect availability of 24-h care, presenting after usual practice hours to after-hours primary care services or to hospital emergency departments (ED) (Ifediora and Rogers 2017;Payne et al 2017). The number of ED presentations increased by 67% from 4.5 million in financial year 2004-05 to 7.5 million in 2015-16 (Australian Institute of Health and Welfare 2009; Australian Institute of Health and Welfare 2016), with the rate of increase exceeding the rate of population growth (Payne et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, patients expect availability of 24-h care, presenting after usual practice hours to after-hours primary care services or to hospital emergency departments (ED) (Ifediora and Rogers 2017;Payne et al 2017). The number of ED presentations increased by 67% from 4.5 million in financial year 2004-05 to 7.5 million in 2015-16 (Australian Institute of Health and Welfare 2009; Australian Institute of Health and Welfare 2016), with the rate of increase exceeding the rate of population growth (Payne et al 2017). An estimated 10-40% of ED presentations represent clients who could be managed in primary care and detract ED services and resources from more urgent presentations (Payne et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, need-driven factors were the most important predictors of appropriate ED use [ 55 ]. Conversely, common factors for inappropriate ED use include greater trust in the hospital than in the primary care setting [ 56 ], greater convenience [ 57 ], time saving [ 58 , 59 ], or lack of primary care access [ 60 ]. One Taiwanese nationwide validation study reported that an increase in the availability of ambulatory care physicians or facilities did not decrease non-emergency ED use [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concluded that ED utilization varies by insurance status, socioeconomic status, race, and other sociodemographic factors [19,72]. Common factors for inappropriate ED use include greater trust in the hospital than in primary care [48] or greater convenience [38] and time savings [73,74]. Previous Billings/NYU-ED classi cation algorithm [40,75] designed to monitor different groups' ambulatory care sensitive conditions [76] or safety-net role of ED use [40,77].…”
Section: Discussionmentioning
confidence: 99%